Phylogeny, structural patterns, and polymorphisms in Dyckia spp. from the Espinhaço mountain range based on complete chloroplast genome - João Victor Da Silva Rabelo-Araujo; Ana Flávia Francisconi; Caroline Bertocco Garcia; Cássio Van Den Berg; Otavio Batista de Castro Ribeiro; Ana Paula da Silva Marques; Matheus Scaketti; Ana Cristina Silva Amoroso Anastacio; Maria Imaculada Zucchi (Frontiers in Plant Science)
Dyckia spp. are xeromorphic bromeliads, with diversity centered in the ferruginous rocky outcrops of the Espinhaço mountain Range in Brazilian tropical savana. Due to their recent radiation – during the Pliocene – along with their vast phenotypic plasticity and the limited herbarium records, many species in the genus present challenges for correct identification and the development of robust conservation strategies. We sequenced the complete chloroplast genome of six rare Dyckia species in an effort to identify hotspots of diversity that could serve as molecular markers capable of distinguishing species and elucidating phylogenetic relationships within the genus. The plastome sizes of the species ranged from 159,689 bp to 159,264 bp, and the GC content was highly consistent across all species, varying narrowly between 37.2% to 37.3%. Despite the high structural similarity, polymorphism analyses identified three regions of high polymorphic diversity—the clpP1 and psa1 genes, and the intergenic spacer region between trnT and the trnL — that may serve as molecular markers within the genus. Additionally, we detected a high number of SSRs (637), dispersed repeats (208), SNPs (1035), and indels (823) among the species compared to other bromeliads. Phylogenetic analyses using whole plastid genomes showed low variability among species, associating them with their geographic distribution. These results not only highlight the structural variability of the Dyckia plastid genome but also provide new molecular tools for the identification of related species, enhancing the development of conservation protocols for these bromeliads.